2003
DOI: 10.1046/j.1365-4362.2003.01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to patient compliance in the treatment of acne vulgaris

Abstract: Demographic factors, such as gender, race, method of payment for medical services, and type of therapy prescribed, were more important in determining appointment keeping behavior than were patient attitudes and beliefs, previous therapy, or severity of acne. Although there was no correlation between appointment keeping and knowledge of the condition, knowledge of the medication, severity of acne, age, or previous medical treatment, relationships were observed between demographic factors and appointment keeping. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…Almost one-third of the 144 patients in this study continued to take their medications despite missing significant numbers of appointments. 18 Several limitations should be noted: first, our findings may not be generalized to a broader population because these patients were predominantly African-American women. Second, patients who participate in clinical trials may be more adherent than those who do not, although nonadherence rates reported in our study is reflective of that reported by other investigators.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Almost one-third of the 144 patients in this study continued to take their medications despite missing significant numbers of appointments. 18 Several limitations should be noted: first, our findings may not be generalized to a broader population because these patients were predominantly African-American women. Second, patients who participate in clinical trials may be more adherent than those who do not, although nonadherence rates reported in our study is reflective of that reported by other investigators.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings resonate with those of other investigators who suggested that clinic appointment attendance is not an accurate proxy for medication-taking behavior. 15,17,18 For example, in the study by Landers et al, attendance at a worksite hypertension program was not associated with the number of medication changes or reported medication sideeffects. 15 Similarly, data from 622 epileptic patients involved in a clinical trial indicated that 60% of the patients who were nonadherent with prescribed anti-seizure medications recorded 100% appointment-keeping behavior.…”
Section: Discussionmentioning
confidence: 98%
“…This corroborates findings by other investigators. Ngwenga et al, in a face-toface/telephone interview found forgetfulness to be the major cause of non-attendance among diabetic patients in South Africa [19]. In Ireland, a study in a gastroenterology outpatient clinic identified forgetting appointments and feeling well as reasons for no-show [20] while Mohammed and Al-Doghaither (2002) cited forgetfulness and lack of transport as the most common reasons for non-attendance [21].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians sometimes encounter a fair number of patients who prematurely discontinue topical acne medications due to local adverse effects. 7 Because both adapalene and benzoyl peroxide (BPO) may alter integrity of the skin barriers, the potential irritation effect of this combination gel could be problematic. 8 Compared with Caucasians, Asians have complained of irritations more often in previous studies of topical retinoid and clindamycin/BPO.…”
Section: Introductionmentioning
confidence: 99%